Key kinematic parameters in a low-loss power splitter written by femtosecond laser micromachining. (13th March 2018) - Peyton, R; Guarepi, V; Videla, F; Torchia, G A
Abstract: In this work we design, fabricate and characterize a 1  ×  2 Y-branch power splitter based on simplified coherent coupling. This device was constructed by type II waveguide structures inscribed by a direct femtosecond laser writing technique in x-cut lithium niobate crystal. First of all, a theoretical study that links the kinematic and writing fluence of the process is developed, which allows us to establish the design trade-off and justify the best geometry chosen. Then, the design was optimized and tested by using commercial software, resulting in a compact and low-loss photonic circuit. The efficiency of the proposed device is compared with two others: a curved and a straight splitter. Finally, the experimental results were compared with simulations and then a statistical analysis of multiple comparisons was also conducted, obtaining 3.7 dB  ±  0.1 dB insertion losses and 4.5% of the unbalanced coupling ratio.